2019
DOI: 10.18388/abp.2018_2789
|View full text |Cite
|
Sign up to set email alerts
|

The The influence of high doses of α-tocopherol on the content of selected trace elements in the liver of developing chicken embryos in experimentally induced 2,3,7,8-tetrachlorodibenzo-p-dioxin intoxication

Abstract: A chicken embryo develops in ovo without access to a constant circulating maternal nutrient supply, and therefore all necessary nutrients are initially stored in the yolk, and with progressive development are transferred to the liver, where they are taken up in response to various needs. Fluctuations in hepatic trace elements correlate with their mobilization from egg stores. 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) intoxication causes liver damage by production of free radicals, while α-tocopherol is a well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Kloser et al [ 17 ] proved that α-tocopherol, in addition to overcoming oxidative stress related to the generation of ROS by dioxins, possesses the blocking properties of an aryl hydrocarbon receptor. Previous studies have shown that when high doses of tocopherol are used in dioxin-contaminated animals, there is a decline in the concentration of diagnostic markers of inflammation and in the results of liver function tests [ 9 , 10 , 18 , 19 ]. In addition, it was found that acetylsalicylic acid (ASA) significantly reduces the amount of TCDD binding to cytosolic AhR, as well as potentially blocking the signal transduction initiated by exposure to the dioxin [ 11 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kloser et al [ 17 ] proved that α-tocopherol, in addition to overcoming oxidative stress related to the generation of ROS by dioxins, possesses the blocking properties of an aryl hydrocarbon receptor. Previous studies have shown that when high doses of tocopherol are used in dioxin-contaminated animals, there is a decline in the concentration of diagnostic markers of inflammation and in the results of liver function tests [ 9 , 10 , 18 , 19 ]. In addition, it was found that acetylsalicylic acid (ASA) significantly reduces the amount of TCDD binding to cytosolic AhR, as well as potentially blocking the signal transduction initiated by exposure to the dioxin [ 11 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic feature of dioxins, including TCDD, is stability under all environmental conditions, bioaccumulation and atmospheric or oceanic transport over long distances . The main sources of human and animal exposure to dioxins are food (over 90%) and polluted air. TCDD is toxic to living organisms and causes, for example, inflammation of tissues and organs.…”
Section: Introductionmentioning
confidence: 99%